2019
DOI: 10.1039/c9tc01724k
|View full text |Cite
|
Sign up to set email alerts
|

Janus NLO dendrimers with different peripheral functional groups: convenient synthesis and enhanced NLO performance with the aid of the Ar–ArFself-assembly

Abstract: Janus NLO dendrimers with different peripheral functional groups were constructed by combining the “Janus” topology and the Ar–ArF self-assembly effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…As TCNE is continuously added to the solution, the absorption peak at 470 nm gradually increased until the absorption peak at 376 nm decreased to a minimum after the addition of 2 equivalents of TCNE, which indicates the complete conversion of Q to Q-11. In previous works [ 21 , 22 , 23 , 24 , 25 , 26 ], click chemistry is shown to be efficient and free of side reactions. In Figure 2 a, the production of extinction dots at 348 nm and 405 nm proves that the click reaction is side-reaction free.…”
Section: Preparation and Researchmentioning
confidence: 99%
“…As TCNE is continuously added to the solution, the absorption peak at 470 nm gradually increased until the absorption peak at 376 nm decreased to a minimum after the addition of 2 equivalents of TCNE, which indicates the complete conversion of Q to Q-11. In previous works [ 21 , 22 , 23 , 24 , 25 , 26 ], click chemistry is shown to be efficient and free of side reactions. In Figure 2 a, the production of extinction dots at 348 nm and 405 nm proves that the click reaction is side-reaction free.…”
Section: Preparation and Researchmentioning
confidence: 99%
“…DP-4l and DP-6l in this work, especially DP-4l, turned out to be a better solution to combine "dendritic topology + structural heterogeneity + easy synthesis." To an extent, the DPs here and their synthetic strategies seemed to revisit the balance of performance and preparation, where the former emphasized its key role on structural heterogeneity and the latter on controllable dendron grafting and site reactivation 44,45 . It is a possible way to construct multifunctional DPs, not only limited to NLO polymers, but many other materials in various fields.…”
Section: Nlo Propertiesmentioning
confidence: 99%
“…A variety of dendritic structure have been explored to develop high performance second-order NLO materials so far, including dendrimers, dendronized polymers, hyperbranched polymers (HBPs), and dendronized hyperbranched polymers (DHPs). Furthermore, it has been manifested that rational regulation of the topological structure for a dendritic NLO material is highly necessary to maximize the final NLO effects. , For example, we demonstrated that by simply changing the dendrimer structure from “cone-like” to “global-like”, the corresponding d 33 values can be remarkably improved from 194 to 246 pm/V based on the same azo-chromophores . Further introducing the azo-chromophores into an intelligent X-shaped Janus structure, the resulting dendrimers, even with a relatively low generation, can surprisingly produce the largest d 33 value up to 299 pm/V for azo-chromophores due to the achievement of highly ordered noncentrosymmetric arrangement during the poling process .…”
Section: Introductionmentioning
confidence: 99%